2016
DOI: 10.12697/fce.2016.53.13
|View full text |Cite
|
Sign up to set email alerts
|

The lichens of forest rocky communities of the hill Muroigora (Arkhangelsk Region, Northwest Russia)

Abstract: Abstract:The present study reports 188 species and 2 subspecies of lichens and allied fungi from forest rocky communities of the hill Muroigora situated in the Arkhangelsk part of the National park "Vodlozersky" (Arkhangelsk Region, NW Russia).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 1 publication
(3 reference statements)
0
11
0
Order By: Relevance
“…Formerly known in Arkhangelsk Region only from Onezhsky District (Tarasova et al, 2019). Distribution in neighboring territories: Republic of Karelia (Tarasova et al, 2016), Republic of Komi (Hermansson et al, 2006), and Murmansk Region (Konstantinova et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formerly known in Arkhangelsk Region only from Onezhsky District (Tarasova et al, 2019). Distribution in neighboring territories: Republic of Karelia (Tarasova et al, 2016), Republic of Komi (Hermansson et al, 2006), and Murmansk Region (Konstantinova et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Our earlier publications (Tarasova et al, 2015(Tarasova et al, , 2016 contain detailed overview of history of lichenological studies in the territory of Arkhangelsk Region. Currently, diversity of lichens and allied fungi in Arkhangelsk Region is becoming increasingly studied (Konoreva et al, 2019b;Tarasova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The physiogeographic and climatic characteristics of this area were described in detail in our previous papers (Tarasova et al, 2015;2016).…”
Section: Methodsmentioning
confidence: 99%
“…Continued lichen inventories are necessary to increase knowledge about the biodiversity of such an reference area with high conservation value communities. The lichen studies on the ridge Windy Belt began recently, nonetheless, they have revealed a high species diversity (269) of lichens and allied fungi in this area (Tarasova et al, 2015(Tarasova et al, , 2016. For example, the oceanic lichen Platismatia norvegica was found on the ridge top (Olovgora Mountain) for the first time for the territory of the European part of Russia (Tarasova, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently 188 species were also reported from the Muroigora, which is located in the Arkhangelsk portion of the Park (Tarasova et al, 2016).…”
Section: Study Areamentioning
confidence: 99%